An observational study comparing ormeloxifene with evening primrose oil for benign breast diseases - Anupam Banerjee,; Dipan Mukhopadhyay,; Tapati Mondal,; Swarup Chakraborty, (Asian Journal of Medical Sciences, 2023)
Background: Fibroadenosis, popularly termed aberrations of normal development and involution (ANDI), is by far the most common female breast presentation to a surgeon. ANDI accounts for the most common breast lumps in women <30 years of age. Mastalgia, a significant spectrum of ANDI, is usually classified as (1) cyclical mastalgia (more common) and (2) non-cyclical mastalgia. Breast nodularity, the other spectrum of ANDI may either present as a predominant feature or coexist with mastalgia. Aims and Objectives: The aims of this study were to comparatively study ormeloxifene and evening primrose oil with respect to regression of fibroadenosis and mastalgia and evaluate their side effects. Materials and Methods: This prospective study was conducted in the Department of General Surgery of Calcutta National Medical College and Hospital, Kolkata from February 15th, 2021 to February 14th, 2022, after obtaining prior Institutional Ethical Committee Clearance. Two hundred and eighty patients were equally divided into two groups of 140 in each and screened for inclusion in this study. Results: At the start of treatment, Group A (Ormeloxifene) presented with a mean visual analog scale (VAS) score value of 5.71, while patients of Group B presented with a similar mean VAS score value of 5. Group B recorded a VAS score of 4.50 at the end of the 6th month, while Group A recorded a significant downhill slope of negligible mean VAS score value of 0.80 at the of the 6th month. In breast nodularity gradings too, Group A showed significant down staging of grades returning, 95% confidence interval at the end of 6th month as 1.144, while 2.280 was recorded for Group B. Conclusion: Benign breast disease is a common presenting problem in females of reproductive age. Ormeloxifene can be a better alternative to evening primrose oil in both cyclical and non-cyclical types of mastalgia. Larger trials are however required, to finally conclude on.